Activities of the wintering party of the 28th Japanese Antarctic Research Expedition, 1987-1988 - Yoshikuni Ohyama (National Institute of Polar Research, 1989)
The wintering party of the 28th Japanese Antarctic Research Expedition performed its activities at Syowa and Asuka Stations from 1987 to 1988. The wintering activities at Asuka Station had commenced from this season by eight men, and have already been reported by M. AYUKAWA. The wintering party at Syowa Station composed of 29 personnel has newly started two long-term scientific programs. One was the Antarctic Climate Research which was recommended by the Scientific Committee on Antarctic Research with reference to the World Climate Research Program. The other was the Studies of Terrestrial Ecosystems which was the Japanese program in response to the international program of Biological Investigations of Terrestrial Antarctic Systems. The routine and fundamental observations comprising aurora, geomagnetism, ionosphere, meteorology, oceanography and seismology were performed as in the preceding years. A seismic observation using the triangular telemetric system was carried out. Two circum-Antarctic balloons were launched in December 1987.